GLI1-altered mesenchymal tumor involving the parietal pleura: case report and literature review - Zhong, Yuanli; Li, Baizhou; Wang, Gangping; Liu, Yuqing; Chen, Zhenwei (Frontiers in Oncology, 2025)
GLI1-altered mesenchymal tumors represent a rare category of soft tissue tumors that have recently been incorporated into the classification of head and neck soft tissue tumors in the fifth edition of the World Health Organization (WHO) classification. However, their precise nature remains undefined, and they have yet to be assigned an ICD code. These tumors are predominantly located in the head and neck region and display distinctive pathological morphology and molecular characteristics. We present the first documented case of a GLI1-altered mesenchymal tumor occurring in the pleura. Microscopic examination revealed that the tumor was composed of ovoid-to-round and vaguely epithelioid cells, as well as a few spindle cells, all exhibiting a uniform morphology and organized in a nested and reticular arrangement, accompanied by a rich capillary network in the stroma. Immunohistochemical staining demonstrated positivity for CD56, S-100, and SMA. Next-generation sequencing (NGS) revealed a PTCH1-GLI1 fusion. Based on the morphological and immunophenotypic characteristics, molecular studies confirmed the diagnosis of a GLI1-altered mesenchymal tumor. At the 15-month follow-up, the patient was alive. We conducted a review of all cases of recurrence and metastasis, concluding that this type of tumor has a distinct propensity to metastasize to the lungs. The tumor exhibits malignant potential, and factors such as its occurrence outside the head and neck region, high-grade histological morphology, active mitosis (>5/10HPF), necrosis and PTCH1-GLI1 fusion are all considered potential risk factors.